2015
DOI: 10.1007/s00284-015-0934-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer Parasporin Toxins are Associated with Different Environments: Discovery of Two Novel Parasporin 5-like Genes

Abstract: Cry toxins are primarily a family of insecticidal toxins produced by the bacterium Bacillus thuringiensis (Bt). However, some Cry toxins, called parasporins (PSs), are non-insecticidal and have been shown to differentially kill human cancer cells. Based on amino acid homology, there are currently six different classes of parasporins (PS1-6). It is not known what role parasporins play in nature, nor if certain PSs are associated with Bt found in particular environments. Herein, we present ten parasporin-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…proteins are yet to be classi ed (Poornima et al, 2010;Gonzalez et al, 2011;Ammons et al, 2016). Among these six classes of parasporin, only PS1 kills cancer cells by activating apoptotic signaling pathway causing from attenuation of cellular protein and DNA synthesis, and by increasing in ux of calcium ions (Katayama et al,2007).…”
Section: Bacillus Thuringiensismentioning
confidence: 99%
“…proteins are yet to be classi ed (Poornima et al, 2010;Gonzalez et al, 2011;Ammons et al, 2016). Among these six classes of parasporin, only PS1 kills cancer cells by activating apoptotic signaling pathway causing from attenuation of cellular protein and DNA synthesis, and by increasing in ux of calcium ions (Katayama et al,2007).…”
Section: Bacillus Thuringiensismentioning
confidence: 99%
“…The sequences of the two cry genes were identical with the previously reported cry64Ba and cry64Ca genes, respectively (GenBank accession no. KC960014) (11). In addition, we conclude that the cry64Ba and cry64Ca genes are plasmid encoded since these genes were located at scaff_269 in the genome draft sequence and a BLASTN search revealed that scaff_269 shows 99% identity with plasmid pYGD98 from the Bacillus thuringiensis strain YGd22-03.…”
Section: Resultsmentioning
confidence: 78%
“…Here, we report novel features of two Bt Cry toxins, Cry64Ba and Cry64Ca, which were previously identified from Bt isolates showing toxicity against HepG2 cancer cells (11). We cloned both genes and confirmed that Cry64Ba and Cry64Ca proteins expressed together in an acrystalliferous Bt strain showed high insecticidal activity against rice planthoppers but no cytotoxicity against HepG2 cells.…”
mentioning
confidence: 56%
“…In preliminary screening test using sheep erythrocytes, it was observed that parasporal proteins obtained from the 60 strains were capable of inducing a strong hemolytic response. It is now known that such hemolysis is affected by broad-spectrum cytolysins (Cyt proteins) that are active on a wide range of invertebrate and vertebrate cells [17]. A total of 1,684 strains that lacked obvious hemolytic parasporal proteins were then examined for in vitro cytocidal activity against MOLT-4 cells (human leukemic T-cells).…”
Section: Introductionmentioning
confidence: 99%